First aid emergencies community. - Garner, Simon; Breitenmoser, Kurt; Godjali, Aldi; Weerakoon, Dinushi; McKenzie, Ben; De Robbio, Michael; Video Education Australasia (Bendigo : Video Education Australasia, 2013)
Accidents and injuries occur without warning. This program provides a rundown of the issues involved, and the main types of injuries that occur in the community and how they should be treated. It includes what to do in an emergency, legal and moral aspects of first aid, fractures, dislocations, strains and sprains, neck, head and spinal injuries, hypothermia and hyperthermia, and CPR (cardio-pulmonary resuscitation) - (both hands-only, and hand and mouth procedures). With clear verbal and visual information, it portrays some typical scenarios in public places where immediate first aid intervention is required and demonstrating the correct ways to administer relevant procedures.
What to do in an emergency -- Legal and moral aspects of first aid -- Fractures, dislocations, strains and sprains -- Neck, head and spinal injuries -- Hypothermia and hyperthermia -- Credits -- End program.
Closed-captioned.
VEA12046/D.
'Special thanks to MFB Metropilitan Fire Brigade, Trevor Bowen, Meg Rayner ; Healthcorp.
Keywords: First aid in illness and injury; Life skills; Sports Injury and Safety